Becoming Balinese Islam: Bale Banjar and Subak in Islamic Village of Segara Katon, Karangasem, Bali. - I Nyoman Yoga Segara (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2019)
Muslims in Karangasem are relatively homogeneous since they originate from the Sasak tribe, Lombok. The story of the conquest of the kingdom in Lombok by the Kingdom of Karangasem turned out to be the beginning of the Sasak tribe Muslims occupying 25 of the 26 Islamic villages, except the Saren Javanese Islamic Village from Demak, Java. The pattern of settlement through the Islamic Village further spreads around the Kingdom of Karangasem. Sasak tribe Muslims were then currently placed in the catu land which belonged to the kingdom. One of the numerous fascinating Muslim villages is Segara Katon. Some of its residents are still of Balinese origin as the result of the marriage of converted Gamongan people to Segara Katon women. Another uniqueness is the existence of the bale banjar which even though it has been acknowledged as a form of acculturation between Hinduism and Islam in the past, yet, it has been left standing although its function has presently begun to shift along with the establishment of the Nurul Jihad Mosque. The long history and traditions that they experienced in a relatively long time were made a fabulous social capital to survive in the midst of various changes, including being active and creative in strengthening peaceful relations with Hindus through multiple local wisdom. To be able to explore data and analyze how Balinese Muslim people in Segara Katon see themselves and their social world, field research was carried out through interviews, observation, and document studies.